2002
DOI: 10.1093/jac/dkf124
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of roxithromycin on the local levels of bone-resorbing cytokines in an experimental model of murine osteomyelitis

Abstract: These results indicate that roxithromycin suppresses the local expression of IL-1beta and TNF-alpha, and may exhibit an anti-inflammatory effect in this osteomyelitis model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Bone wax was used to seal the access burr hole and sequential study of the infectious process and establishment of osteomyelitis was observed. Both Sottnik et al (Sottnik et al , 2010) and Yoshii et al (Yoshii et al , 2002a; Yoshii et al , 2002b) utilize a transcortical hole in the proximal part of the tibia with implanted S. aureus seeded suture material as the source of the osteomyelitis. Varoga et al (Varoga et al , 2008; Varoga et al , 2009) modified a rat model initially described by Lucke et al (Lucke et al , 2003b), in which an access hole in the proximal part of the tibia allowed access to the medullary canal for the introduction of an inoculum.…”
Section: Literature Review Of Animal Modelsmentioning
confidence: 99%
“…Bone wax was used to seal the access burr hole and sequential study of the infectious process and establishment of osteomyelitis was observed. Both Sottnik et al (Sottnik et al , 2010) and Yoshii et al (Yoshii et al , 2002a; Yoshii et al , 2002b) utilize a transcortical hole in the proximal part of the tibia with implanted S. aureus seeded suture material as the source of the osteomyelitis. Varoga et al (Varoga et al , 2008; Varoga et al , 2009) modified a rat model initially described by Lucke et al (Lucke et al , 2003b), in which an access hole in the proximal part of the tibia allowed access to the medullary canal for the introduction of an inoculum.…”
Section: Literature Review Of Animal Modelsmentioning
confidence: 99%
“…The concentration of TNF-␣ in the bone microenvironment in vivo has been estimated to be ∼100-200 ng/g and increase up to 600-1500 ng/g on stimulation with pathogenic agents. (51) In the bone microenvironment, cell sources that are likely candidates for TNF-␣ production include the osteoblastic cells, (40) adipocytes, (52) endothelial cells, (53) T lymphocytes, and the monocytes/macrophages, (54) which have been shown to affect bone resorption in vivo, whereas studies have also indicated the capacity of TNF-␣ to regulate osteoclastic activity in an autocrine fashion in vitro. (55) Importantly, addition of a TNF-␣-neutralizing antibody both in vitro and in vivo significantly blocked the OAB-related osteoclastogenic and the bone resorptive response.…”
Section: Figmentioning
confidence: 99%
“…The injury can also be contaminated from the insertion of a surgical material into the wound such as a pre-inoculated silk suture (Yoshii, 2002a;Yoshii et al, 2002b), pre-inoculated agarose beads (Marriott et al, 2004;Marriott et al, 2005) or a pre-inoculated collagen sheet (Inzana et al, 2015b).…”
Section: Inoculation Methods and Dosementioning
confidence: 99%